Accumulation of Short Bouts of Non-Exercise Daily Physical Activity is Associated with Lower Visceral Fat in Japanese Female Adults - Ayabe, M.; Kumahara, H.; Morimura, K.; Sakane, N.; Ishii, K.; Tanaka, H. (International Journal of Sports Medicine, 2013)
The purpose of the present investigation was to assess the relationship between bouts of very short daily physical activity (PA) lasting <10 min with obesity and abnormal fat distributions. A total of 42 females (age 50±6 years, height 156±5 cm, body weight 54±8 kg, body mass index 22±3 kg/m2) participated in the present investigation. Computed tomography was used to evaluate the area of visceral adipose tissue and subcutaneous adipose tissue (VAT and SAT). All participants wore a pedometer with a one-axial accelerometer (Lifecorder, Kenz, Japan) in order to determine their frequency (bouts/day) of PA and moderate to vigorous intensity PA (MVPA). The total frequency of PA and MVPA, including all bout durations, was not significantly associated with the body fat distribution. The frequency of PA lasting longer than 3 min and 5 min, and MVPA lasting longer than 1 min and 3 min were significantly associated with the area of the VAT (p<0.05). A smaller area of VAT was associated with a higher frequency of PA and MVPA lasting 1–5 min. The present investigation did not find that very short bouts of PA lasting<1 min played a significant role in controlling abdominal fat distribution.
Keywords: exercise; accelerometer; pedometer; obesity